2022
DOI: 10.1371/journal.pone.0273880
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, balance, and bicycling in older adults

Abstract: Falls are a critical public health issue among older adults. One notable factor contributing to falls in older adults is a deterioration of the structures supporting balance and overall balance control. Preliminary evidence suggests older adults who ride a bicycle have better balance than those who do not. Cycling may be an effective intervention to prevent falls among older adults. This study aims to objectively measure the relationship between bicycling, physical activity, and balance for older adults. Older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Interestingly, using technology, it was successfully attempted to quantify the risk of falls in older individuals due to poor balance (Estévez-Pedraza, et al, 2021). It was also demonstrated that cycling could be an effective intervention to improve balance and reduce the risk of falls in older individuals (Baughn, et al, 2022). The age is represented by the mean ± standard deviation or the median (inter-quartile range).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, using technology, it was successfully attempted to quantify the risk of falls in older individuals due to poor balance (Estévez-Pedraza, et al, 2021). It was also demonstrated that cycling could be an effective intervention to improve balance and reduce the risk of falls in older individuals (Baughn, et al, 2022). The age is represented by the mean ± standard deviation or the median (inter-quartile range).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed accelerometer procedures can be found in the previously published protocol (Grimes et al, 2022a). These procedures have been used in previous studies (Grimes et al, 2022b;Baughn et al, 2022).…”
Section: Physical Activitymentioning
confidence: 99%